Ambiguidade, anúncio publicitário e interpretação de texto - Santana, Simone Menezes Costa de (2015)
Studies have shown that reading and comprehension skills are the most relevant problems in not only Portuguese classes, but also in Education in general. It is fundamental then that schools take some measures as to encourage reading, text comprehension, and the use and recognition of different oral and written genres with which readers come across daily. Taking that into consideration, the objective of this report is to present the results of the first phase of the application of the Activities Module, titled Ambiguity, advertisement and text comprehension, whose purpose, taking into account the study of ambiguity in advisements, is to motivate students to do reading and text comprehension activities, in a 9th grade class. That module was theoretically and methodologically designed according to Cosson´s (2004) perspective. According to him, a Didactic Sequence (DS) involves the following steps: motivation, introduction, reading and interpretation. As theoretical support, Cançado (2004), Martins (1994), Marcuschi (2008) and Koch & Elias (2012), among others, were also important references since they understand reading as a dialogue involving reader/text/writer. The analysis of this first phase revealed a positive balance, because the students satisfactorily corresponded to all proposed suggestions, showing interest, actively participating in the reading, text interpretation and comprehension activities, focusing on the phenomenon of ambiguity in advisements. This reinforces the idea that children and teenagers surrender in a more open and immediate way when motivational proposals brings up a model that lets them interact creatively. One more aspect that is positive about the module is the possibility of establishing a closer connection between theory and practice, enabling similar activities involving other contents and topics to take place.